GARAP GENDING JULA-JULI LANTARAN GAYA MALANG - Iska Aditya Pamuji; darsono darsono (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2017)
AbstractThe research on Gending Jula-juli Lantaran in Malang style is based on the writer’s interest in the emergence of a new gending. This gending is treated in a different way from the general interpretation of gending in East Javanese style karawitan. The presence of this gending forms the background to the two problems addressed in this research. First, the role of Malang style tembang macapat in the interpretation of gending Jula-juli; second, the interpretation of Gending Jula-juli in Malang style. This research uses a qualitative method with emphasis on an analytical descriptive and interpretative approach. The concept of garap (interpretation / treatment) is used to examine the problems related to the interpretation of gending Jula-juli in Malang style.Gending Jula-juli Lantaran is a development of the general gending Jula-juli and uses a variety of treatment not commonly found in gending Jula-juli. The gending places emphasis on the interpretation of tembang macapat (sung verse) in Malang style. The composition of this gending brings alignment or balance between the development of gending and tembang macapat. This phenomenon presents a new model of interpretation of Malang style gending and provides new knowledge about Malang style karawitan and East Javanese karawitan in general. Keywords: Interpretation, Gending, Jula-juli Lantaran. AbstrakPenelitian tentang Gending Jula-juli Lantaran gaya Malang didasari atas ketertarikan peneliti terhadap kemunculan gending baru. Gending tersebut memiliki garap yang berbeda dari gending secara umum pada karawitan gaya Jawa Timuran. Kehadiran gending tersebut melatarbelakangi munculnya dua permasalahan. Pertama adalah mengenai peran tembang macapat gaya Malang dalam garap gending Jula-juli. Permasalahan kedua berkaitan dengan garap gending Jula-juli Lantaran gaya Malang. Gending Jula-juli Lantaran merupakan pengembangan dari gending Jula-juli secara umum serta memilki garap yang beragam dan tidak ditemukan dalam gending Jula-juli secara umum. Gending tersebut memberikan penekanan terhadap kemunculan garap yang terletak pada tembang macapat gaya Malang. Terciptanya gending tesebut membawa kesejajaran atau keseimbangan antara perkembangan gending dan tembang macapat. Fenomena ini bisa menjadi suatu model garap baru pada gending - gending gaya Malang, memberi pengetahuan baru pada karawitan gaya Malang serta karawitan Jawa Timuran pada umumnya. Kata Kunci: Garap, Gending, Jula-juli Lantaran.